A quantitative approach for measuring process innovation: a case study in a manufacturing company - ÖZTEMEL, ERCAN; AYHAN, MUSTAFA BATUHAN (TAYLOR & FRANCIS LTD, 2013)
Process management and innovation arguably remain among the concepts under focus of recent researches since there is no significantly outstanding method to measure and monitor the level of innovation in the manufacturing processes over a particular time period taking the fundamental activities of manufacturing processes into account. Although there are various studies relevant to process improvement, manufacturing processes are not focused on in the literature. This paper presents a novel performance indicator, called degree of process innovation, for monitoring and measuring innovation in manufacturing processes based on the four most important components among the fundamental activities of a manufacturing system. The components are namely Average Labour Utilisation, Cumulative Bottleneck Ratio, Unit Production Time and Unit Production Cost. The idea behind this approach has flourished on the basis of an indicator proposed in the literature to measure the general organisational improvements. The scope of that indicator has been narrowed down to manufacturing processes to accurately reflect the state of the manufacturing processes. The proposed approach has been verified with a case study in manufacturing industry, where each of the four sub-indicators was calculated based on the data provided and aggregated into the degree of process innovation. The innovation degree is successfully indicated.
Keywords: manufacturing systems; process innovation; degree of process innovation